Positive Effect of Severe Nakagami-m Fading on the Performance of Multiuser TAS/MRC Systems with High Selection Gain - Chia-Chun Hung; Ching-Tai Chiang; Rong-Ching Wu; C. Lee (International Journal of Antennas and Propagation)
This paper investigates the positive effect of severe Nakagami-m fading on the performance of multiuser transmit antenna selection/maximal-ratio combining (TAS/MRC) systems with high selection gain. Both amount of fading (AF) and symbol error rate (SER) of M-QAM are derived as closed-form expressions for integer m. For arbitrary m, the AF and the SER are expressible as a single infinite series of Gamma function and Gauss hypergeometric function, respectively. The analytical results lead to the following observations. First, the SER performance can demonstrate the positive effect of severe Nakagami-m fading on multiuser TAS/MRC systems with high selection gain. Second, the AF performance only exhibits the negative impact of severe fading regardless of high selection gain. Last, the benefit of severe fading to the system performance diminishes at high signal-to-noise ratio (SNR).